Combination of ground-based and satellite remote sensing measurements over Limassol - Nisantzi, Argyro; Mamouri, Rodanthi-Elisavet; Akylas, Evangelos; Hadjimitsis, Diofantos G. (My University, 2013)
According to the International Panel of Climate Change (IPCC, 2007) there are still uncertainties in climate change predictions due to the impact of aerosols in the solar irradiance. The scattering procedure of aerosols depends strongly on their shape and size distribution while lidar techniques could give the vertical distribution of them. Southeastern Mediterranean is affected by air masses of different sources thus layers with complicate aerosol composition are frequently observed over Cyprus. A backscatter lidar has been established at Cyprus University of Technology's (CUT) premises (34°N, 33°E) since 2010, in order to provide vertical profiles of the aerosol optical properties such as backscatter coefficient and particle depolarization ratio. More than 2 years of daily measurements have been analyzed for the period of May 2010 to May 2012. From this dataset, there are almost 45 CALISPO coincidence overpasses at a distance of less than 105km from the location of the ground-based lidar and from those two cases were selected. Both, ground based and space born active remote sensing techniques were used in order to characterize aerosol layers in the free troposphere over SE Mediterranean. The layers of CALIPSO and CUT's lidar observations have been examined with respect to their origin, in order to retrieve the backscatter coefficient and the particle depolarization ratio at 532nm. The analysis of the presented cases, together with the air mass back-trajectories calculations, in accordance with depolarization retrievals, show that non-spherical particles originated from Africa whereas marine layer consist of spherical particles. Furthermore aerosol optical properties such as Angström exponents (AE) derived from the sunphotometer belonging to the AERONET network at Limassol city were used complementary in order to support our analysis.
Keywords: CALIPSO; Depolarization; Lidar; Remote sensing; Southeast Mediterranean